ANALISIS RISIKO INVESTASI SAHAM TUNGGAL SYARIAH DENGAN VALUE AT RISK (VAR) DAN EXPECTED SHORTFALL (ES) - Saepudin, Yunus; Yasin, Hasbi; Santoso, Rukun (Jurnal Gaussian, 2017)
One measure that can be used to estimate risk is Value at Risk (VaR). Although VaR is very popular, it has several weakness that VaR not coherent causes the lack of sub-additive. To overcome the weakness in VaR, an alternative risk measure called Expected Shortfall (ES) can be used.  The porpose of this research objective are to estimate risk by ES and by using VaR with Monte Carlo simulation. The data we used are the closing price of Unilever Indonesia stocks that consistently get into Jakarta Islamic Index (JII). To make VaR become easier for people to understand, an application is made using GUI in Matlab. The Expected Shortfall results from the calculation using 99% confidence level that may be experienced is at 0.039415 show that the risk exceed the VaR it is at 0.034245.  For 95% confidence level that may be experienced is at 0.030608 show that the risk exceed the VaR it is at 0.024471. For 90% confidence level that may be experienced is at 0.026110 show that the risk exceed the VaR it is at 0.019172. Show that the greater the level of confidence that is used the greater the risk will be borne by the investor.Keywords: Risk, Value at Risk (VaR), JII, Expected Shortfall (ES).